Outbreak of H5N2 highly pathogenic avian Influenza A virus infection in two commercial layer facilities: lesions and viral antigen distribution. (September 2016) - Arruda, Paulo H. E.; Stevenson, Gregory W.; Killian, Mary L.; Burrough, Eric R.; Gauger, Phillip C.; Harmon, Karen M.; Magstadt, Drew R.; Yoon, Kyoung-Jin; Zhang, Jianqiang; Madson, Darin M.; Piñeyro, Pablo; Derscheid, Rachel J.; et al.
The largest outbreak of highly pathogenic avian Influenza A virus (HPAIV) infection in U.S. history began in December 2014 resulting in the euthanasia of millions of birds and collateral economic consequences to the U.S. poultry industry. We describe 2 cases of H5N2 HPAIV infection in laying hens in Iowa. Following a sharp increase in mortality with minimal clinical signs, 15 dead birds, from 2 unrelated farms, were submitted to the Iowa State University Veterinary Diagnostic Laboratory. Common lesions included diffuse edema and multifocal hemorrhage of the comb, catarrhal exudate in the oropharynx, and multifocal tracheal hemorrhage. Less common lesions included epicardial petechiae, splenic hemorrhage, and pancreatic necrosis. Influenza A virus nucleoprotein was detected by immunohistochemistry in multiple cell types including ependymal cells, the choroid plexus, neurons, respiratory epithelium and macrophages in the lung, cardiac myocytes, endothelial cells, necrotic foci in the spleen, Kupffer cells in the liver, and necrotic acinar cells in the pancreas. Real-time polymerase chain reaction and sequencing confirmed H5N2 HPAIV with molecular characteristics similar to other contemporary U.S. H5N2 HPAIVs in both cases.